Nanoscale domain imaging and the electromechanical response of zinc oxide nanorod arrays synthesized on different substrates - Abubakar, Shamsu; Liew, Josephine Ying Chyi; Sin, Tee Tan; Sagadevan, Suresh; Talib, Zainal Abidin; Paiman, Suriati (Elsevier Editora, 2021)
Zinc oxide nanorods (ZnO NRs) have gained considerable research interest due to their robust energy conversion efficiency. In the present work, ZnO NRs arrays were pinpointed to probe their electromechanical response under strain conditions. ZnO seed was sputtered on different substrates by radio frequency magnetron sputtering (RF) technique at 80 W constant power and 3.49 x 105 mbar base pressure. The X-ray diffraction patterns exhibit hexagonal wurtzite structure with preferred c-axis crystal directions in the (002) plane. The average thickness of the seed layer for all the samples was estimated at around 214.6 nm. Surface roughness and morphologies of the nanorods have been characterized by atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM), respectively. FE-SEM images show homogeneous growth in different directions on substrates. The average diameters of ZnO NRs on silicon, glass and ITO were 51, 58 and 61 nm, respectively. The average length of all the nanorods on the substrates were measured around 1e2 mm. The local piezoresponse measurements conducted on two selected domain regions of the nanorod arrays had been characterized by piezoresponse force microscopy (PFM) to confirm the switching-piezoelectric behavior.